Effect of grain boundary on the friction coefficient of pure Fe under the oil lubrication. (March 2021) - Adachi, Nozomu; Matsuo, Yasutaka; Todaka, Yoshikazu; Fujimoto, Mikiya; Hino, Masahiro; Mitsuhara, Masatoshi; Oba, Yojiro; Shiihara, Yoshinori; Umeno, Yoshitaka; Nishida, Minoru
Abstract: In this study, the effect of grain boundary on the frictional behavior under the oil-lubricated condition was investigated by varying the grain size (crystallite size) of the pure Fe samples prepared via physical vapor deposition. A high fraction of grain boundary in the sample yielded a low friction coefficient μ in the case of a lubrication oil that formed a chemisorbed film on the surface of the material. Thick absorbed layer formed on the surface was observed only in the sample with high fraction of grain boundary. These results indicate that a disordered structure in the vicinity of grain boundary preferentially forms chemisorbed films and reduces μ by protecting the surface of the material. Highlights: Grain boundary fraction in a pure Fe sample was controlled by changing a sputtering thickness while keeping smooth surface. Enhancement of a formation of chemisorbed film by grain boundary was presumable occurred under oil-lubricated condition. Under the lubrication which forms no chemisorbed film the effect of hardness on friction coefficient was negligibly small. It was suggested that the sample with high fraction of grain boundary forms thick chemisorbed film.